Vasomotor symptoms and management of women undergoing treatment for breast cancer: literature review with focus on the therapeutic potential of cytoplasmic pollen extract - Stefano Lello; Ida Paris; Angelo Cagnacci; Donata Sartori; Salvatore Caruso; Aldo Iop (Taylor & Francis Group, 2023)
Objective Effective management of vasomotor symptoms (VMS) in patients undergoing treatment for breast cancer (BC) represents a critical but frequent unmet need. This review summarizes the epidemiology, pathophysiology, and clinical features of VMS in patients with BC and provides a synopsis of the complementary and alternative medicine (CAM) approaches in relieving VMS with a focus on purified cytoplasm of pollen (PCP).Methods The literature on VMS epidemiology, pathophysiology, clinical burden, and CAM treatment in healthy women and patients with BC was reviewed.Results VMS are common in patients with BC undergoing hormonal treatment and negatively impact quality of life, leading to treatment discontinuation in up to 25% of patients with detrimental impact on risk of BC recurrence and overall survival. CAM approaches to treat VMS in patients with BC include vitamin E, phytoestrogens, and black cohosh, even if there is a lack of solid evidence to guide clinicians in the choice of treatment. PCP, obtained according to standards of good manufacturing practice, has a definite pharmacological mechanism of action, is devoid of estrogen activity, and has shown clinical efficacy on menopause-associated symptoms with a favorable safety profile and high compliance. As such, it appears to represent a valid management option to improve quality of life in patients with pre- and postmenopausal BC.Conclusions Physicians should actively investigate the presence and impact of VMS in patients receiving therapy for BC. Additional and appropriately sized randomized clinical trials are needed to provide clear evidence on how to best meet the needs of patients with BC suffering from menopause-associated symptoms.